The Influence of Leadership Style on Employee Performance through Readiness For Change Post Acquisition Company - Keke Tamara Fahira; Rozaq Muhammad Yasin (University of Darussalam Gontor, 2023)
The current period of acquisition strategy is an effective and efficient way to relocate assets in the economy, especially the banking sector. The acquisition brought many changes to the organization. The research aims to answer the influence of post-acquisition Leadership Style on employee performance through Readiness for Change as an intervening variable. This research method uses Partial Least Square (PLS). This study uses a non-probability sampling method to collect data. Primary data is used in this study by distributing 100 sample questionnaires to employees at BRI AGRO bank. The finding is that leadership style has a significant effect on employee performance post-acquisition through readiness for change. The results of the study, can be concluded that in order to improve the performance of employees at Bank BRI AGRO, they can maintain and improve their leadership style. In addition to mediating research variables, Readiness for Change also has a direct influence on employee performance.